Does Teachers’ Creativity Promote Economic Learning Outcomes? The Role of Student Creativity Quotient - Ari Saptono; Fanny Nurhayati; Suparno Suparno (Universitas Negeri Malang, 2021)
This study aims to determine the effect of teacher teaching creativity and student creativity quotient on economic learning outcomes in class X state senior high schools in East Jakarta. This study uses a quantitative method with a correlational approach. The population of this study was 11163 students of class X high school in East Jakarta, the sample selection technique used multistage random sampling, and a sample of 208 students was selected. The data collection for the teacher's teaching creativity and the creativity quotient used a questionnaire, while the learning outcomes used secondary data. This study used Path analysis. Results showed that teachers' teaching creativity significant influence on student learning outcomes, the creativity quotient insignificant influence on student learning outcomes, teacher teaching creativity significant influence on creativity quotient, and teachers' teaching creativity, mediated by creativity quotient, insignificant effect on student learning outcomes. The finding of this study implies that the teacher's teaching creativity can increase the creativity quotient of students and students' learning outcomes of economics.